Debates on the Holocaust. - Lawson, Tom (Issues in historiography., 2010)
Debates on the Holocaust is the first attempt to survey the development of Holocaust historiography for a generation. It analyses the development of history writing on the destruction of the European Jews from just before the end of the Second World War to the present day, and argues forcefully that history writing is as much about the present as it is the past. The book guides the reader through the major debates in Holocaust historiography and shows how all of these controversies are as much products of their own time as they are attempts to uncover the past. Debates on the Holocaust will app.